Hubungan Pengetahuan dan Dukungan Keluarga dengan Kepatuhan Kunjungan Ulang Peserta Program Rujuk Balik di Klinik Induk Biddokkes Polda Kalimantan Tengah - Yuliani Kristy; Takesi Arisandy; Nia Pristina (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2024)
The Return Referral Program (RRP) provides healthcare services to patients with stable chronic conditions at primary healthcare facilities. Non-adherence is commonly observed in the treatment of chronic diseases that require long-term care. Adherence is a crucial component for the success of treatment. At the Central Kalimantan Police's Biddokkes Main Clinic, many patients with chronic diseases do not adhere to their treatment, failing to attend follow-up visits as instructed by their doctors on the scheduled dates. Knowledge affects a patient's adherence to therapy and their adherence behavior, and family support is needed to improve RRP participants' adherence. This study aims to identify the effect of knowledge and family support on adherence to follow-up visits among RRP participants at the Central Kalimantan Police's Biddokkes Main Clinic. Methods: This correlational study uses a cross-sectional approach to examine the relationship between knowledge and family support and adherence to follow-up visits among RRP participants at the Central Kalimantan Police's Biddokkes Main Clinic using a questionnaire. The sample consisted of 64 RRP participants registered at the clinic, selected through simple random sampling, and analyzed using Chi-Square tests. Results: The study found significant relationships between knowledge (p Value=0.000) and family support (p Value=0.000) and adherence to follow-up visits among RRP participants at the Central Kalimantan Police's Biddokkes Main Clinic. Conclusion: Knowledge and family support are significantly related to adherence to follow-up visits among RRP participants. The role of nurses as educators for clients and their families can be enhanced to provide knowledge about the importance of active participation in RRP activities for the treatment of chronic patients, aimed at improving the quality of life.